Analysis of herbivore-responsive long noncoding ribonucleic acids reveals a subset of small peptide-coding transcripts in Nicotiana tabacum - Jin, Jingjing; Meng, Lijun; Chen, Kai; Xu, Yalong; Lu, Peng; Li, Zhaowu; Tao, Jiemeng; Li, Zefeng; Wang, Chen; Yang, Xiaonian; Yu, Shizhou; Yang, Zhixiao; et al. (Frontiers in Plant Science, 2022)
Long noncoding RNAs (lncRNAs) regulate many biological processes in plants, including defense against pathogens and herbivores. Recently, many small ORFs embedded in lncRNAs have been identified to encode biologically functional peptides (small ORF-encoded peptides [SEPs]) in many species. However, it is unknown whether lncRNAs mediate defense against herbivore attack and whether there are novel functional SEPs for these lncRNAs. By sequencing Spodoptera litura-treated leaves at six time-points in Nicotiana tabacum, 22,436 lncRNAs were identified, of which 787 were differentially expressed. Using a comprehensive mass spectrometry (MS) pipeline, 302 novel SEPs derived from 115 tobacco lncRNAs were identified. Moreover, 61 SEPs showed differential expression after S. litura attack. Importantly, several of these peptides were characterized through 3D structure prediction, subcellular localization validation by laser confocal microscopy, and western blotting. Subsequent bioinformatic analysis revealed some specific chemical and physical properties of these novel SEPs, which probably represent the largest number of SEPs identified in plants to date. Our study not only identifies potential lncRNA regulators of plant response to herbivore attack but also serves as a valuable resource for the functional characterization of SEP-encoding lncRNAs.